Trajetórias formativas de educadores da EJA: fios e desafios - Ana Paula Ferreira Pedroso (2015)
The Youth and Adult Education (EJA), like any educational process, constitutes an educational modality structured based on the findings about the specifics of their subjects. Accordingly, it is assumed that the profile of the professionals working in this area must also be different. However, studies have shown that the vast majority of teachers in this field of education has no specific training. Because of theseobservations, this research had as object of study the educational background of teachers in the field of adult education, focused in the context of a public school in the town of Belo Horizonte (RME-BH). More specifically, answering to the following questions: How is the formative trajectory of educators from that school focused in youth and adults? How is the entering of teachers in adult education? To what extent the pedagogical practice contributed and / or contributes to the training as a teacher? Which are the specifities of this teaching? Which are the enablers and inhibitors aspects of training to the development of teaching? In this perspective, in order to investigate the building processes of educators of youth and adults of that school, it was proposed, for the realization of this research, conducting a qualitative study using documentary research, observation of the meetings focused on teacher training and semi-structured interviews with those educators. Importantly, this research, in addition to collect the paths taken by these teachers in their formative processes, also offered guidelines that can contribute to the progress of discussions on the issue of teacher training in adult and youth education.